Clinical application prospects of traditional Chinese medicine as adjuvant therapy for metabolic reprogramming in colorectal cancer - Zhexian, Liu; Xingqi, Guo; Xinxin, Dong; Tong, Xia; Siping, Ma; Yanxi, Li (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) is the second leading cause of cancer-related deaths globally and the third most commonly diagnosed malignancy, posing a major threat to public health. Clinical manifestations such as altered bowel habits (e.g., constipation, diarrhea, or pencil-thin stools), rectal bleeding, and abdominal pain or bloating may indicate CRC. A hallmark of CRC is metabolic reprogramming, which enables tumor cells to meet the bioenergetic and biosynthetic demands of rapid proliferation and survival. This reprogramming encompasses dysregulated glycolysis, amino acid metabolism, and lipid metabolism, collectively driving tumor growth, invasion, angiogenesis, and therapeutic resistance. Targeting metabolic reprogramming has emerged as a promising strategy in CRC therapy. Inhibitors of key metabolic enzymes and signaling pathways involved in glycolysis have demonstrated efficacy in preclinical and early clinical studies. Additionally, Traditional Chinese Medicine (TCM) has attracted increasing interest for its potential to modulate tumor metabolism. This review examines current evidence on marketed drugs, TCM, and the underlying metabolic mechanisms implicated in CRC treatment. While TCM shows promise as a complementary therapeutic approach, further research is essential to validate its clinical utility and mechanistic underpinnings.